2010
DOI: 10.1111/j.1442-2042.2010.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of naftopidil on the quality of life of patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia: A prospective study

Abstract: Objectives:  To investigate the benefit of α1‐adrenoceptor antagonist naftopidil on the quality of life (QOL) of patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (BPH/LUTS). Methods:  A total of 99 men with BPH/LUTS were prospectively recruited. The Short Form‐8 (SF‐8) was used for generic QOL assessment and each parameter was compared with the norm in these patients. Longitudinal changes were evaluated using the SF‐8 and the International Prostatic Symptoms Score (I‐PSS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 14 publications
0
24
0
3
Order By: Relevance
“…Effectiveness of naftopidil at a high dose for voiding symptoms can be explained by pharmacokinetics/pharmacodynamics of the agent in vivo and its effect on α 1 -adrenoceptor antagonists/ α 1 -adrenoreceptors interaction [13]. Storage symptoms are considered to represent those of BPH-related overactive bladder [14], and most recent basic studies on α 1 -adrenoceptor antagonists/ α 1 -adrenoreceptors in the lower urinary tract may account for the dose-dependent efficacy of naftopidil for improving storage symptoms [14, 15]. Unfortunately, our study cannot clarify the reason for improved storage symptoms including nocturia with naftopidil; the complexity of the mechanism of nocturia made us refrain from explicating this phenomenon [16].…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of naftopidil at a high dose for voiding symptoms can be explained by pharmacokinetics/pharmacodynamics of the agent in vivo and its effect on α 1 -adrenoceptor antagonists/ α 1 -adrenoreceptors interaction [13]. Storage symptoms are considered to represent those of BPH-related overactive bladder [14], and most recent basic studies on α 1 -adrenoceptor antagonists/ α 1 -adrenoreceptors in the lower urinary tract may account for the dose-dependent efficacy of naftopidil for improving storage symptoms [14, 15]. Unfortunately, our study cannot clarify the reason for improved storage symptoms including nocturia with naftopidil; the complexity of the mechanism of nocturia made us refrain from explicating this phenomenon [16].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 39 , focusing on health-related QoL (HRQoL), described significant improvement of IPSS and King's Health Questionnaire Score domains after 12 weeks of treatment with naftopidil, particularly for patients with overactive bladder. A recent study of Komiya and colleagues 40 …”
Section: Other Clinical Studiesmentioning
confidence: 97%
“…Komiya et al demonstrated that LUTS/BPH impaired generic QOL evaluated by the Short Form-8 (SF-8), that was improved by naftopidil treatment 58. Awa et al showed that naftopidil significantly improved 7 domains, though not general health perceptions and social limitations, in the King’s Health Questionnaire (KHQ) having 9 domains consisting of 21 questions 59…”
Section: Qol and Naftopidilmentioning
confidence: 99%